การตรวจสอบความสามารถในการรวมตัวสำหรับผลผลิตและองค์ประกอบผลผลิตในสายพันธุ์ข้าวโพดหวานพิเศษโดยวิธี Line x Tester - วสุวัฒนกุล, วรวรรณ; จิระเกียรติกุล, เยาวพา; หาระโคตร, พรชัย (Thai Journal of Science and Technology, 2021)
In super sweet corn improvement, selecting a high potential inbred line is important to provide a high yielding hybrid and good yield components. Therefore, the objective of this study was to study combining ability for yield and yield component in the S2 generation of super sweet corn lines. The twenty super sweet corn lines were crossed with two testers in a line x tester mating design. The parental lines, 40 crosses, and 2 check varieties were evaluated in the rainy and dry seasons 2019/2020. The results indicated that variations of the dominant gene were more than additive gene effects for all studied traits except cob replacement height. L13 and L20 super sweet corn lines had high means and GCA values for yield, whereas L13 had a high GCA value for cob length and cutting percentage, and L5 lines had a high GCA value for total soluble solids. In addition, all super sweet corn crosses with a high SCA value were derived from the S2 generation lines or tester, especially T2 tester, which had a high GCA value. This study indicated that L13 and L20 lines had high performance to develop as super sweet corn inbred lines and used as new hybrids with high yield and yield components in the future. Moreover, T2 was a good tester and suitable for the super sweet corn breeding program.